PREVALENCE AND FACTORS ASSOCIATED WITH STUNTING AND FALTERING GROWTH AMONG INFANTS WITH VERY LOW-BIRTHWEIGHT AGED 16–24 MONTHS AT A TERTIARY CENTER - Siak, Bee Leng; Musa, Maizatul Akmar; Lee, Yee Lin (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION There is limited study in Malaysia on the prevalence of faltering growth and stunting among babies with very low birth weight (VLBW) during the first 24 months of life. This study aimed to evaluate the prevalence of faltering growth and stunting in infants with VLBW after NICU discharge and identify factors related to post-discharge faltering growth and stunting. METHODOLOGY We conducted a retrospective study at a tertiary center in Selangor among infants with VLBW who completed three follow-up consults at corrected age intervals (CA) of 3 to <9 months, 9 to <16 months, and 16–24 months old. RESULT The prevalence of post-discharge faltering growth was 39.6%, 31.8%, and 24.8% at the respective age intervals. At CA 16 to 24 months, the prevalence of stunting was 23.2%. The percentage of infants with faltering growth who experienced stunting at CA 3 to <9 months rose from 51% to 70% at CA 16 to 24 months. Small for gestational age (SGA), extremely low birth weight (ELBW), male gender, faltering growth at discharge, and length of stay >66 days (LOS) were all significant risk factors for faltering growth at all age intervals. Infants on steroids for chronic lung disease and intraventricular hemorrhage had an increased risk of faltering growth only at CA 3 to <9 months old. Among these risk factors, SGA, ELBW and male gender were identified as predictors for both faltering growth and stunting at 16–24 months of age. Maternal characteristics did not show significant association with post-discharge faltering growth and stunting. CONCLUSION Most of the infants who had faltering growth also experienced stunting at 16 to 24 months old. This study highlights the importance of adequate nutrition early on targeting at-risk groups to prevent faltering growth and reduce the likelihood of stunting in infants with VLBW.